2019
DOI: 10.1038/s41467-019-11691-y
|View full text |Cite|
|
Sign up to set email alerts
|

Females show more sustained performance during test-taking than males

Abstract: Females tend to perform worse than males on math and science tests, but they perform better on verbal reading tests. Here, by analysing performance during a cognitive test, we provide evidence that females are better able to sustain their performance during a test across all of these topics, including math and science (study 1). This finding suggests that longer cognitive tests decrease the gender gap in math and science. By analysing a dataset with multiple tests that vary in test length, we find empirical su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 49 publications
(42 reference statements)
12
38
0
Order By: Relevance
“…With respect to gender differences in neuropsychological performance among Palestinian children, three main functions were identified: phonetic fluency, sustained attention, visuomotor coordination. These findings coincide with that of other studies in which girls presented a better performance in language tests [ 35 , 36 ], visuomotor coordination [ 37 , 38 ] and sustained attention [ 39 , 40 ]. However, there is no scientific consensus regarding these differences.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to gender differences in neuropsychological performance among Palestinian children, three main functions were identified: phonetic fluency, sustained attention, visuomotor coordination. These findings coincide with that of other studies in which girls presented a better performance in language tests [ 35 , 36 ], visuomotor coordination [ 37 , 38 ] and sustained attention [ 39 , 40 ]. However, there is no scientific consensus regarding these differences.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, in this context, it is of interest to note that a previous study by Walsh et al [ 17 ] reported a weak positive association between radiologist productivity and quality of resident teaching. The results of Walsh et al [ 16 ] and those of the present study suggest clinical productivity to be accompanied by other professional virtues in radiology practice.…”
Section: Discussionsupporting
confidence: 74%
“…The latter is in line with the results of a previous study that reported women to generally outperform men on knowledge tests about clinical science concepts essential for patient care under supervision [ 15 ]. Of interest, another study has shown that females are better able to sustain their performance during a long test regardless of their relative advantage or disadvantage in the domain being assessed [ 16 ]. This was hypothesized to be due to the fact that males have been found to experience higher levels of boredom on activities with a long duration, which might cause impaired performance after some time of test-taking [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalized nature of the female advantage in school performance contradicts the existing stereotypes that girls excel exclusively in languages, while boys only excel in math and science (Tiedemann, 2000;Skaalvik and Skaalvik, 2004;Sáinz and Eccles, 2012). According to a recent study, girls' better use of extra time at the end to finish tests on account of their ability to sustain performance can explain gender differences in score performance (Balart and Oosterveen, 2019). Unfortunately, according to Voyer and Voyer (2014), women's better performance over that of their male counterparts throughout compulsory schooling in most countries has received little attention as a global phenomenon.…”
Section: Introductionmentioning
confidence: 95%